2015
DOI: 10.1016/j.ijrobp.2015.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Computed Tomography–Based Volumetric Brachytherapy Planning for Cervical Cancer

Abstract: SummaryImage guided brachytherapy (IGBT) has been adopted by multiple centers in recent years for the treatment of cervical cancer. The clinical outcomes are promising, with favorable results compared with those of conventional techniques. Previously reported studies have used primarily magnetic resonance imagingdbased treatment planning. We report the clinical outcomes of a novel hybrid computed tomographyebased IGBT technique. At 2 years, local control was excellent, with low rates of treatment toxicity. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…In previous reports, Nomden et al reported that the mean HR-CTV D90 in EQD2 was 84 Gy [9]. Simpson et al reported that the mean HR-CTV D90 was 86.3 Gy [12]. Although our HR-CTV D90 per implant was equivalent to that in other institutions [8,9], Radiotherapythe goal of total D90 was set lower because the use of the CS technique might hinder delivery of higher D90.…”
Section: Hr-ctvmentioning
confidence: 57%
See 4 more Smart Citations
“…In previous reports, Nomden et al reported that the mean HR-CTV D90 in EQD2 was 84 Gy [9]. Simpson et al reported that the mean HR-CTV D90 was 86.3 Gy [12]. Although our HR-CTV D90 per implant was equivalent to that in other institutions [8,9], Radiotherapythe goal of total D90 was set lower because the use of the CS technique might hinder delivery of higher D90.…”
Section: Hr-ctvmentioning
confidence: 57%
“…There are an increasing number of published reports regarding treatment results of IGABT for cervical cancer as shown in Table 4 [8][9][10][11][12][14][15][16][17]. In 2011, Pötter et al retrospectively analyzed 156 patients with FIGO stage IB to IVA cervical cancer treated by IGABT at Medical University of Vienna [8].…”
Section: Reported Treatment Resultsmentioning
confidence: 99%
See 3 more Smart Citations